2020
DOI: 10.3390/gidisord2010002
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Microbiome Effectiveness: A Role for Ingestible Sensors

Abstract: Across the world there is an increasingly heavy burden of noncommunicable diseases related to obesity, mental health, and atopic disease. In a previous publication, we followed the developing idea that that these conditions arise as our microbiome loses diversity, but there seems to be no generally applicable way to assess the significance of this loss. Our work revisited the findings of the African studies by Denis Burkitt who reported that the frequency of what he called Western diseases were inversely propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 60 publications
0
15
0
Order By: Relevance
“…In principle, an ingestible sensor, a pill-like device bearing a detector and a transmitter, could be developed so as to measure the levels of such species upon exposure to foodstuffs containing substances such as dietary fibre and polyphenols, for example. The resultant response may indicate the degree of dysbiosis and, with help of "omic" approaches [71,72], generate personalised, accurate, and potentially massively applied treatments to assist in finding a method of amelioration, if not an actual cure [73].…”
Section: Semiochemicals: From Single Cells To Multicellular Animalsmentioning
confidence: 99%
“…In principle, an ingestible sensor, a pill-like device bearing a detector and a transmitter, could be developed so as to measure the levels of such species upon exposure to foodstuffs containing substances such as dietary fibre and polyphenols, for example. The resultant response may indicate the degree of dysbiosis and, with help of "omic" approaches [71,72], generate personalised, accurate, and potentially massively applied treatments to assist in finding a method of amelioration, if not an actual cure [73].…”
Section: Semiochemicals: From Single Cells To Multicellular Animalsmentioning
confidence: 99%
“…Although considered in more detail later, the use of an ingestible sensor designed to respond to the presence of semiochemicals [24] would help to connect microbial composition with microbiome function [62]. In principle it should prove possible to track several different semiochemicals in parallel.…”
Section: Microbiome Investigationmentioning
confidence: 99%
“…We have suggested that such chemicals act alongside hormones to facilitate gut movement thus ensuring that the microbiome receives adequate nutrition, allowing for events such as pregnancy or famine. In principle these allomones may be monitored by means of ingestible sensors and thereby provide information about the state of microbiome effectiveness [62].…”
Section: The Microbiome As a Mutualistic Entity: Allomones And Kairomonesmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction of the microbiome with different nutrients can be real‐time quantitatively measured. [ 118 ]…”
Section: Componentsmentioning
confidence: 99%